Ḍawʼ al-sârî li-maʻrifat ḫabar Tamîm al-Dârî =(On Tamim al-Dari and his waqf in Hebron) : critical edition, annotated translation and introduction - Maqrīzī, Aḥmad ibn ʻAlī, 1364-1442. (Bibliotheca Maqriziana, 2014)
The present book investigates three short late Mamluk treatises about land properties (waqf) in the Palestinian city of Hebron, which the prophet Muhammad granted to Tamīm al-Darī. The treatise entitled Ḍawʾ al-sārī li-maʿrifat ḫabar Tamīm al-Dārī by al-Maqrīzī (d. 845/1442) is the core of the book. It is edited here for the first time on the sole basis of the copy corrected by the author. A facsimile of the manuscript is also provided at the end of the book. In order to illuminate the discourse on property rights and donation that prevailed in the Mamluk period and al-Maqrīzī's position, two additional treatises dealing with the same issue are included. The first is al-Ǧawāb al-ǧalīl ʿan ḥukm balad al-Ḫalīl by Ibn Ḥaǧar al-ʿAsqalānī (d. 852/1448). The second is al-Faḍl al-ʿamīm fī iqṭāʿ Tamīm by al-Suyūṭī (911/1505). The three texts are fully translated and annotated and preceded by a thorough introduction.